Analisis Produktivitas Produksi PT. Bapak Bakery Badung Bali - Afianti, Evita Zuyyina; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): MaretDO - 10.24843/JRMA.2020.v08.i01.p13, 2020)
Bapak Bakery is one of the bread companies in Bali. This company has never taken productivity measurements. The company only uses the profits of sale production as a benchmark of its success achievement. PT. Bapak Bakery has problem in the field of production, namely lack of availability of raw materials which resulted in hampered production process so that consumer demand could not be fulfilled. The purpose of this study is to measure the level of production productivity, analyze the contribution of productivity ratio component and recommendation for PT. Bapak Bakery productivity improvement. The study uses the Objective Matrix (OMAX) method. In this study there are 5 ratios that are used as criteria in measuring productivity. The ratio is included in the criteria of efficiency, effectiveness and inferentiality. The productivity measurement results show that the lowest productivity index value is in March 2018 which was 175.3 and the highest value obtained was in July which was 501.6. Contribution analysis of productivity ratio component PT. Bapak Bakery who obtained the highest productivity value, namely ratio 1 with value of 830.7 and the lowest productivity value is ratio 3 and 4 with a value of 738. Recommendation of productivity improvement obtained ratio 1 in the amount of Rp. 131.724.436, ratio 2 is Rp 1.830.959 , ratio 3 is 6.471 hours, ratio 4 is Rp 600.064.834 and ratio 5 is 504 hours. Keywords:  Bread production, productivity measurement, Objective Matrix (OMAX)